Effectiveness of Personal Finance among Selected Skilled – Working Expatriates in the Kingdom of Bahrain - Dr. Steve Salamat Guansi; Emad Sadeq Ebrahim (International Journal of Engineering and Management Research, 2018)
In the study entitled “Effectiveness of Personal Finance among Selected Skilled – Working Expatriates in the Kingdom of Bahrain”, the research sought answers on the following specific problems and drawn inferences that relatively identified factors on personal finance. Specifically, the research included fifty respondents having twenty – five (25) males and twenty - five (25) skilled – working expatriates who are connected with various companies in the Kingdom. Through survey – questionnaires, data were gathered, collected, and were used as basis of analysis subject to statistical treatments that include frequency count, weighted means and comparison through t – test. The study has inferred the level of effectiveness of personal finance among selected skilled – working expatriates as Effective with a combined average weighted mean of 4.20 and with a test result of Not Significant leading to the decision to fail to reject the null hypothesis. while the degree of seriousness of the problems encountered by selected skilled – working expatriates revealed that their top difficulty is financial wellness factored by salary reasons, compensation, debt and liabilities and the inflations in the prices across almost basic demands and social and living costs.